Trapping effects and surface/interface recombination of carrier recombination in single- or poly-crystalline metal halide perovskites - Lobo, Ntumba; Kawane, Takuya; Matt, Gebhard; Osvet, Andres; Shrestha, Shreetu; Levchuk, Ievgen; Brabec, Christoph; Kanak, Andrii; Fochuk, Petro; Kato, Masashi (Japanese Journal of Applied Physics, 2022)
The lifetime of a carrier is a crucial parameter for solar cell materials, and metal halide perovskite materials are promising for solar cell applications. In this study, we observed carrier recombination using time-resolved photoluminescence (TR-PL) and microwave photoconductivity decay (mu-PCD) in metal halide perovskite materials: NH3CH3PbI3 (MAPbI(3)), NH3CH3PbBr3 (MAPbBr(3)), and CsPbBr3 with single- and poly-crystalline structures. By comparing the decay curves of TR-PL and mu-PCD, we found trap levels in the band gap for all the materials. We employed two excitation wavelengths for the mu-PCD measurements, and we observed faster mu-PCD signal decays for short wavelength excitation for MAPbBr(3) and CsPbBr3. Additionally, we established that the poly-crystals exhibited faster decay compared with the single crystals for MAPbBr(3) and CsPbBr3. Therefore, we concluded that there are significant contributions of the interface and surface recombination on carrier recombination for MAPbBr(3) and CsPbBr3, but not for MAPbI(3).
CRIS-Team WoS Importer:2022-12-16